Professors-in-Training or Precarious Workers? Identity, Coalition Building, and Social Movement Unionism in the 2015 University of Toronto Graduate Employee Strike - Birdsell Bauer, Louise (Labor Studies Journal, 2017)
In this article, I argue that graduate employees took on the political identity of precarious workers who face job insecurity and income insecurity, drawing attention to the casualization of work in the academic labor market in Canada, and the cost of undertaking graduate studies in Canadian universities. Their argument appealed to media, faculty, undergraduate students, and supportive media, which was key to building solidarity and public support for graduate employees’ struggle. Building on social movement unionism literature, I show how this identity moved the debate away from the bargaining table and into broader coalition building, suggesting a broader social movement unionism among academic workers.